MAPALUS ACTIVITY-BASED REVENUE MANAGEMENT ANALYSIS FOR SUSTAINABLE GOVERNANCE - Mardjun, Joya Thasya Ikrimah; leniwati, Driana; Wahyuni, Endang Dwi; Mawardi, Fahmi Dwi (Polytechnic of State Finance STAN, 2024)
This study focuses on the integration of revenue management and cultural values in Mapalus activities, specifically in managing income obtained from farmers' dues in the Manado region. The study aims to explore the blend of cultural values and income management in Mapalus activities, identify advantages and disadvantages, and develop strategies to maintain transparency, accuracy, and fairness in fund allocation. The interpretive paradigm with a qualitative approach is employed, using a case study research design. Primary data from interviews with key stakeholders and secondary data from accounting reports are utilized. The research highlights the importance of cultural values in revenue management and how they influence decision-making processes. It also emphasizes the role of accounting in maintaining transparency and accuracy in managing funds raised from activities like collecting dues. The findings contribute to a deeper understanding of the unique accounting practices that reflect the values and culture of the Mapalus community.